Nature as an Ecological Asset for Positive Youth Development: Empirical Evidence From Rural Communities - Bowers, Edmond P.; Larson, Lincoln R.; Parry, Benjamin J. (Frontiers in Psychology, 2021)
Despite increasing emphasis on youth contact with nature and associated benefits, research has not examined the direct relationship between adolescents’ nature-based experiences and holistic measures of positive youth development (PYD). This gap may stem from the lack of interdisciplinary work on nature and PYD. Our study integrates multiple disciplinary perspectives to explore direct associations between time in nature, connection to nature, and the five Cs of PYD (competence, connection, confidence, character, and caring) as well as the “sixth” C of contribution. From 2015-2016, we collected data from 587 diverse South Carolina middle school students (57% female, 40% BIPOC) between the ages of 11 and 14 (M age = 12.9) and living in predominantly low-income communities. OLS regression analyses indicated that across all youth, self-reported connection to nature was a consistent positive correlate of overall PYD and each of the individual Cs. Time in nature was associated with overall PYD and competence. Findings demonstrate significant associations between nature-based experiences and PYD and underscore the importance of ensuring that diverse youth can access and enjoy the developmental benefits of nature and nature-based recreation opportunities.